Fast non-line-of-sight imaging with high-resolution and wide field of view using synthetic wavelength holography - Florian Willomitzer (Nature Portfolio, 2021)
Here, the authors present Synthetic Wavelength Holography, an approach for Non-Line-of-Sight imaging. By exploiting spectral correlations in scattered light, the authors transform real world surfaces such as walls or scatterers into High-Resolution, Wide-Field-of-View imaging portals that provide holograms of objects obscured from view.